Pengaruh Intervensi Keperawatan Kombinasi Chewing Gum dan Aromaterapi terhadap Pemulihan Sistem Pencernaan Pasien Post Seksio Sesarea di Ruang Aster RSUD Kota Bandung - Umi Khasanah; Yayat Suryati; Siti Nurbayanti Awaliyah; Tetti Solehati; Murtiningsih Murtiningsih (Wiraraja Medika : Jurnal Kesehatan, 2026)
Cesarean section is a surgical procedure performed to deliver a fetus through an incision in the abdominal wall. Postoperative gastrointestinal recovery is often delayed due to postoperative ileus. Non-pharmacological interventions such as chewing gum and aromatherapy have been reported to accelerate the return of bowel function. This study aimed to analyze the effect of a combination of chewing gum and aromatherapy on gastrointestinal recovery in post-cesarean section patients. This study used a quasi-experimental design with a pretest–posttest nonequivalent control group approach. The study was conducted in November 2024 at RSUD Kota Bandung, involving 40 respondents divided into an intervention group (n=20) and a control group (n=20). Inclusion criteria were post-cesarean section patients who were conscious, hemodynamically stable, and willing to participate. Exclusion criteria included patients with complications or gastrointestinal disorders. Consecutive sampling was applied. The intervention group received chewing gum and peppermint aromatherapy in the early postoperative phase, while the control group received standard care. The study employed a quasi-experimental design without randomization, with the primary outcome being gastrointestinal recovery measured by bowel sounds. The control group received early mobilization, including limb movement 3 hours after spinal anesthesia and repositioning every 3 hours. Data were collected using an observation sheet based on standard operating procedures for bowel sound frequency. The results showed a significant increase in bowel sound frequency in both groups, with a greater effect observed in the intervention group. Additionally, the time to first flatus was shorter in the intervention group, indicating faster clinical recovery of gastrointestinal function. In conclusion, the combination of chewing gum and aromatherapy is effective in accelerating gastrointestinal recovery in post-cesarean section patients and may be considered as a supportive intervention